Penerapan web bamboozle pada mata pelajaran SKI kelas IV MIN Kota Blitar - Sukma, Ftrotul Mutiara (Maliki Interdisciplinary Journal, 2025)
Education is a fundamental pillar in shaping individual character and advancing a nation. With the rapid development of the times, the integration of digital technology has become essential in enhancing the quality of learning. One such innovation is the use of web-based interactive media, such as Baamboozle, particularly in the subject of Islamic Cultural History (Sejarah Kebudayaan Islam – SKI) at MIN Kota Blitar. SKI is often perceived as monotonous due to its memorization-based content, requiring a more creative and engaging approach to stimulate students' interest. This article aims to describe the effectiveness of using Baamboozle in SKI learning through a descriptive qualitative method and literature review technique. Baamboozle is an interactive quiz platform that combines elements of games with learning, enhancing student engagement, group collaboration, and learning motivation. Its use has proven to foster a more dynamic classroom environment, encourage positive competition, and help students better understand the material in an enjoyable manner. However, some limitations of the platform include restricted features, no distinction between teacher and student accounts, and the risk of student passivity in group settings. Despite these weaknesses, its strengths in improving learning effectiveness make Baamboozle a viable tool for hybrid learning models. The integration of such interactive media in SKI learning is recommended as a strategic effort to create higher-quality, innovative, and relevant learning experiences in line with the demands of the digital era.